Trade Policies, Investment Climate, and Exports across Countries - Şeker, Murat (2012)
There is a large body of research that explores international trade as a source of the dispersion in income levels and growth performances across countries. The trade liberalization policies undertaken between 1950 and 2006 led to an almost 30 fold growth in the volume of international trade. However this increase has not been homogeneous across countries. This study investigates a possible reason that prevents convergence of countries in export performance. It shows that regulatory quality, customs efficiency, quality of infrastructure, and access to finance among other factors increase export performance. Furthermore, it shows that countries that are relatively more constrained in accessing to foreign markets benefit more from improvements in investment climate than the countries with easier foreign market access. Hence obtaining a favorable investment climate for private sector development should be an important policy objective for relatively closed economies to achieve convergence in export volumes with countries that have more liberal trade policies.